2019
DOI: 10.21059/buletinpeternak.v43i1.41010
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Salmonella Spp. Bacteria Antibiotic Resistency Indigestion Tract in the Broiler Farms of Subang District

Abstract: This study is aimed to  estimate the prevalence of resistant Salmonella spp., determine the spread of bacterial resistance and investigate the serotypes of bacteria in the chicken’s digestion tract in the broiler farms in Subang District. As many as 74 farms were chosen, five poled caeca samples were taken from each farm and tested for isolation and identification of Salmonella spp. Salmonella isolates obtained were tested antimicrobial susceptibility against 8 antibiotics using the agar dilution method. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…It has been reported that most livestock workers in Subang district, as many as 59% of respondents had common knowledge of antibiotic resistance. As many as 41% of farmer respondents, had a high level of knowledge (Walyani, 2019). The results of a survey on farmer perceptions of antibiotics on farms in West Kalimantan were conducted on 293 commercial broiler breeders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that most livestock workers in Subang district, as many as 59% of respondents had common knowledge of antibiotic resistance. As many as 41% of farmer respondents, had a high level of knowledge (Walyani, 2019). The results of a survey on farmer perceptions of antibiotics on farms in West Kalimantan were conducted on 293 commercial broiler breeders.…”
Section: Discussionmentioning
confidence: 99%
“…The use of antibiotics in feed is closely related to the incidence of resistance to three strains of pathogenic bacteria such as Salmonella, Campylobacter, and Escherichia coli. These bacteria are three of the five main causes of foodborne disease or the cause of death due to foodborne pathogen infection in the United States which are around 90% (Walyani, 2019). Kusumawardani (2016) reported the results of sensitivity tests to chloramphenicol antibiotic in which 2 from 17 strains of E. coli showed resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Gong et al (2022) reported that in a global context, non-typhoidal Salmonella (NTS) leads to 93.8 million cases of gastroenteritis each year, resulting in 155,000 deaths. Investigation in Indonesia found high Salmonella contamination rates in chicken meat (85%), intestine contents (57.5%), and rinse water (52.5%) at traditional markets in Surabaya as reported by Yulistiani et al (2019), meanwhile Walyani et al (2019) reported in Subang, 75% isolates of Salmonella spp. which infects chickens were resistant to antibiotics with a 95% confidence interval (0%-35.4%), one of which was SE.…”
Section: Introductionmentioning
confidence: 88%